2018
DOI: 10.1111/codi.14309
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of complications and mortality following left colectomy with primary stapled anastomosis for cancer: results of a multicentric study with 1111 patients

Abstract: Requirement for TPN was associated with more leaks, complications and mortality. Leakage was presumably responsible for almost half of deaths. Hyperlipidaemia and female gender were associated with lower rates of complications. These findings warrant a better understanding of metabolic status on perioperative outcome after left colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The comorbidity that marked an association with mortality in our study was cardiovascular comorbidity because of ith high prevalence, similar to that reported by Pellino G. et al, who documented this pathology in 52.8% of the patients in their study 19 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The comorbidity that marked an association with mortality in our study was cardiovascular comorbidity because of ith high prevalence, similar to that reported by Pellino G. et al, who documented this pathology in 52.8% of the patients in their study 19 .…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of anastomotic dehiscence is below the average reported in the international literature, our work obtained a 3.8% average, data concordant with work by Martin in 2013 12 , 18 , which reports percentages ranging from 1.2 to 13% in anterior rectal resections by laparoscopy. The use of double staple suture in the creation of the anastomosis was an important factor associated with tumors located less than 10 cm and on the other hand a comparative study of no inferiority describes laparoscopic surgery as a protective factor for anastomotic dehiscence compared to open surgery (9.42% vs 13.47%) 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…As operative morbidity is dependent, among others, on the patient’s age, sex, weight, and health status [ 58 , 59 , 60 ], the potential effects of age, sex, BMI, and ASA and CCI grade on metabolite dynamics in the postoperative period were examined. None were found except for arginine and the arginine-to-ADMA ratio, which decreased directly following surgery exclusively in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…In most patients, it is possible to re-establish gut continuity with an anastomosis, and the surgical wound in the intestine usually heals within 7–10 days. However, a major complication is anastomotic leakage (AL), which occurs in 2–15% of the patients, with the occurrence rate depending on the specific location of the anastomosis [ 1 6 ]. Anastomoses in the right side of the colon have the lowest risk of AL (2–5%), and anastomoses to the rectum have the greatest risk of AL (10–15%).…”
Section: Introductionmentioning
confidence: 99%